2007
DOI: 10.1371/journal.pone.0000469
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Protects Kidney from Renal Ischemia/Reperfusion Injury through the Cholinergic Anti-Inflammatory Pathway

Abstract: Kidney ischemia/reperfusion injury (I/R) is characterized by renal dysfunction and tubular damages resulting from an early activation of innate immunity. Recently, nicotine administration has been shown to be a powerful inhibitor of a variety of innate immune responses, including LPS-induced toxaemia. This cholinergic anti-inflammatory pathway acts via the α7 nicotinic acetylcholine receptor (α7nAChR). Herein, we tested the potential protective effect of nicotine administration in a mouse model of renal I/R in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 32 publications
(50 reference statements)
9
92
1
3
Order By: Relevance
“…We found that I/R injury increased serum creatinine compared with sham at day 1 (1.2 -0.06 vs. 0.35 -0.04 mg/dL, P < 0.01) and day 3 (1.08 -0.14 vs. 0.35 -0.04 mg/dL, P < 0.05) post-I/R (Fig. 1B), which is in agreement with previous reports [8,51]. Mice transplanted with mMSCs exhibited lower serum creatinine levels than the I/R control at day 1 (0.98 -0.06 mg/dL, P = 0.08) and day 3 (0.6 -0.05 mg/dL, P < 0.05) post-I/R, which is also consistent with a previous report [8].…”
Section: S21r-dihdha Treatment Promotes the Capacity Of Mmscs To Msupporting
confidence: 93%
“…We found that I/R injury increased serum creatinine compared with sham at day 1 (1.2 -0.06 vs. 0.35 -0.04 mg/dL, P < 0.01) and day 3 (1.08 -0.14 vs. 0.35 -0.04 mg/dL, P < 0.05) post-I/R (Fig. 1B), which is in agreement with previous reports [8,51]. Mice transplanted with mMSCs exhibited lower serum creatinine levels than the I/R control at day 1 (0.98 -0.06 mg/dL, P = 0.08) and day 3 (0.6 -0.05 mg/dL, P < 0.05) post-I/R, which is also consistent with a previous report [8].…”
Section: S21r-dihdha Treatment Promotes the Capacity Of Mmscs To Msupporting
confidence: 93%
“…The degree of tubular damage was assessed on periodic acid-Schiff diastase (PASD)-stained paraffinembedded tissue sections. The PASD score represents tubular damage, which is visually characterized by necrosis, dilation, cast deposition and loss of brush border [20] . The degree of necrosis was scored by a pathologist in a blinded fashion on a 5-point scale: 0 = no damage, 1 = 10% necrosis of the corticomedullary junction, 2 = 10-25%, 3 = 25-50%, 4 = 50-75%, 5 = more than 75%.…”
Section: Plasma Biochemical Analysis Histology and Immunohistochemistrymentioning
confidence: 99%
“…The degree of necrosis was scored by a pathologist in a blinded fashion on a 5-point scale: 0 = no damage, 1 = 10% necrosis of the corticomedullary junction, 2 = 10-25%, 3 = 25-50%, 4 = 50-75%, 5 = more than 75%. For immunostaining, 4-m tissue sections were incubated with specific antibodies for granulocytes (FITC-labeled anti-mouse Ly6G mAb; BD Biosciences-Pharmingen), apoptosis (rabbit anti-human active caspase-3; Cell Signaling Technology), GFP (rabbitanti GFP IgG; Molecular Probes), HMGB1 (rabbit-anti mouse HMGB1; Abcam), S100B (rabbit anti-S100B; Sigma-Aldrich) or CML ( N -epsilon carboxymethyl lysine) which has been identified as a major structure in advanced glycation end-products (AGE), mouse IgG, Biologo) followed by appropriate secondary antibodies as described before [15,16,[20][21][22][23]. To determine percentage of positive staining on kidney tissue slides, approximately 10 pictures of tissue section were taken under light microscopy (magnification !…”
Section: Plasma Biochemical Analysis Histology and Immunohistochemistrymentioning
confidence: 99%
“…3,4 Lipid peroxidation is an autocatalytic mechanism leading to oxidative destruction of cellular membranes, and their destruction can lead to the production of toxic reactive aldehydic metabolites and cell death. [5][6][7][8] A range of drugs and methods have been tested with the intention to block the pathways of cell injury at different levels and to thereby enhance viability of the kidney challenged by ischemia/ reperfusion stress with variable results, such as: heat shock (interferes with the L-arginine-nitric oxide pathway), 9 antioxidants, 10,11 dipyridamole (increases endogenous adenosine), 12,13 nicotine (inhibit cholinergic antiinflammatory pathway), 14 calcium channel blockers or antagonists, [15][16][17][18] chlorpromazine, 19,20 etc. Chorpromazine (CPZ) is a membrane stabilizer and seems to be able to preserve mitochondria integrity and to reduce phospholipids degradation of microsomal membranes of liver cell provoked by ischemia/reperfusion.…”
Section: Introductionmentioning
confidence: 99%